Early Detection of the Fungal Banana Black Sigatoka Pathogen Pseudocercospora fijiensis by an SPR Immunosensor Method - Luna Moreno, Donato; Sánchez Álvarez, Araceli; Islas Flores, Ignacio; Canto Canche, Blondy; Carrillo Pech, Mildred; Villarreal Chiu, Juan Francisco; Rodríguez Delgado, Melissa Marlene (2019)
Black Sigatoka is a disease that occurs in banana plantations worldwide. This disease is caused by the hemibiotrophic fungus Pseudocercosporaﬁjiensis, whose infection results in a signiﬁcant reductioninbothproductqualityandyield. Therefore,detectionandidentiﬁcationintheearlystages of this pathogen in plants could help minimize losses, as well as prevent the spread of the disease to neighboring cultures. To achieve this, a highly sensitive SPR immunosensor was developed to detect P. ﬁjiensis in real samples of leaf extracts in early stages of the disease. A polyclonal antibody (anti-HF1), produced against HF1 (cell wall protein of P. ﬁjiensis) was covalently immobilized on agold-coatedchipviaamixedself-assembledmonolayer(SAM)ofalkanethiolsusingtheEDC/NHS method.Theanalyticalparametersofthebiosensorwereestablished, obtainingalimitofdetectionof 11.7 µg mL−1, a sensitivity of 0.0021 units of reﬂectance per ng mL−1 and a linear response range for the antigen from 39.1 to 122 µg mL−1. No matrix effects were observed during the measurements of real leaf banana extracts by the immunosensor. To the best of our knowledge, this is the ﬁrst research into the development of an SPR biosensor for the detection of P. ﬁjiensis, which demonstrates its potential as an alternative analytical tool for in-ﬁeld monitoring of black Sigatoka disease.